2017
DOI: 10.1001/jamasurg.2016.3091
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Inferior Vena Cava Filter Insertion in Trauma Patients and In-Hospital and Overall Mortality

Abstract: The research herein demonstrates no significant difference in survival in trauma patients with vs without placement of an IVC filter, whether in the presence or absence of venous thrombosis. The use of IVC filters in this population should be reexamined because filter removal rates are low and there is increased risk of morbidity in patients with filters that remain in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…The discrepancy between our findings and the 30–60% retrieval rates reported in single-center studies calls to question whether the more impressive results at specific institutions truly reflect overall practice patterns in the United States. Our findings corroborate those of a prior study with Medicare data which estimated a 1.2–5.1% retrieval rate 18 (Medicare patients in our cohort had a 2.5% retrieval rate) as well as a large single-center study of trauma patients where the retrieval rate was found to be 8% 20 (trauma patients had a 9.6% retrieval rate in our study). In addition, a recently published study reviewed state-wide filter placement and retrieval rates in New York and reported an overall retrieval rate of 3.5% between 2005 and 2014 21 .…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy between our findings and the 30–60% retrieval rates reported in single-center studies calls to question whether the more impressive results at specific institutions truly reflect overall practice patterns in the United States. Our findings corroborate those of a prior study with Medicare data which estimated a 1.2–5.1% retrieval rate 18 (Medicare patients in our cohort had a 2.5% retrieval rate) as well as a large single-center study of trauma patients where the retrieval rate was found to be 8% 20 (trauma patients had a 9.6% retrieval rate in our study). In addition, a recently published study reviewed state-wide filter placement and retrieval rates in New York and reported an overall retrieval rate of 3.5% between 2005 and 2014 21 .…”
Section: Discussionsupporting
confidence: 92%
“…Hemmila et al analyzed trauma quality collaborative data from 2010 to 2014 and found that prophylactic IVCF placement had no effect on reducing trauma patient mortality, but was associated with an increase in DVT events (OR: 1.83, 95% CI: 1.15 - 2.93, P = 0.01) [ 18 ]. Sarosiek et al performed a retrospective cohort study of patients who underwent IVCF placement at a level 1 trauma center and found no significant difference in survival in trauma patients with or without placement of an IVCF, whether in the presence or absence of venous thrombosis [ 19 ]. As such, they call for re-examination of IVCF use in this patient population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarosiek et al performed a retrospective cohort study of patients who underwent IVCF placement at a level 1 trauma center and found no significant difference in survival in trauma patients with or without placement of an IVCF, whether in the presence or absence of venous thrombosis [ 19 ]. As such, they call for re-examination of IVCF use in this patient population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 91 The placement of an IVC filter does not impact mortality regardless of whether a DVT is present or absent. 92 , 93 While consensus guidelines provide conflicting recommendations and most studies have been observational, among patients diagnosed with an acute proximal DVT or PE who cannot receive adequate therapeutic anticoagulation, an IVC filter should be considered to reduce the rate of recurrent PE without altering the mortality rate. 94 …”
Section: Algorithmmentioning
confidence: 99%